Pseudogout, Neutropenia, and Splenomegaly: A Case of Felty Syndrome - Tali Azenkot; Brittany Chatterton (Annals of Internal Medicine: Clinical Cases)
Felty syndrome is a rare entity of rheumatoid arthritis, neutropenia, and splenomegaly. Patients typically develop the syndrome years after a diagnosis of rheumatoid arthritis. Here, we present a case of a 76-year-old man with history of chronic calcium pyrophosphate crystal deposition disease, or pseudogout, who presented with neutropenic fever. Given his progressive arthralgias and symmetric synovitis on physical examination, serologies were sent and identified a new diagnosis of rheumatoid arthritis. This, together with exclusion of other causes of neutropenia and discovered splenomegaly, led to diagnosis of Felty syndrome.